Course satisfactions and study instruction methods used by cluster of undergraduate students in Universiti Teknologi Malaysia : an analysis / Raja Mayang Delima Mohd. Beta, Ramnah Abd Thani and Shefek Afendi Mohd. Zain - Mohd. Beta, Raja Mayang Delima; Abd Thani, Ramnah; Mohd. Zain, Shefek Afendi (2012)
The main purpose of this study is to identify the differences in the levels of course satisfaction of Universiti Teknologi Malaysia (UTM) students between two different methods of study instruction as well as to suggest ways to increase the students’ performance. In order to help UTM to improve their students’ performance, the study is conducted to identify the factors which contribute to the dissatisfaction of students so that they can be improved. With the intention of measuring the differences between conventional instruction and IT-based instruction, a survey had been conducted with 224 students from Diploma in Electrical Engineering which focused on students from Semester 1 until Semester 3. Respondents are asked to state their perception on the factors pertaining to the level of course satisfaction (Content, Delivery, Quality and Convenience, Challenge of Examination, and Enriching Environment) based on their observation, using a Likert scale of 1 to 5. Frequencies, Descriptive Statistics, One-Way ADOVA, and profile plot are used to reach the goals of the study. The survey was well received and the response return rate comprised 91.07% of the total. The results reveal that the majority of the students appear to be pleased and satisfied with the teaching and learning methods in conventional instruction practiced by UTM. The results also indicate that IT-based instruction became the most important factor that requires improvement by UTM in the aspects of quality and convenience because this scored the lowest in mean value. In conclusion there is a difference in the mean scores of course satisfaction level of students between conventional instruction and IT-based instruction. The study also describes the limitations associated with conducting surveys and provides recommendations for further research.